2021
DOI: 10.1016/j.omto.2021.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Multiple targeted self-emulsifying compound RGO reveals obvious anti-tumor potential in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a highly vascularized, inflammatory, and abnormally proliferating tumor. Monotherapy is often unable to effectively and comprehensively inhibit the progress of HCC. In present study, we selected ginsenoside Rg3, ganoderma lucidum polysaccharide (GLP), and oridonin as the combined therapy. These three plant monomers play important roles in anti-angiogenesis, immunological activation, and apoptosis promotion, respectively. However, the low solubility and poor bioavailability ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Total lipid content, especially triglycerides, was estimated after the addition of ORI to the free fatty acid cell model for 24 h. Furthermore, studies revealed that ORI can enhance autophagy and decrease the liver cells steatosis (Cheng et al., 2021 ). Similarly, ORI, combined with ginsenoside and the fungus Ganoderma lucidum , is reported to enhance immunological processes and ultimately the apoptosis in hepatocellular carcinoma (HCC) cells (He et al., 2021 ).…”
Section: Current Medical Applications – Official Treatment or Traditi...mentioning
confidence: 99%
“…Total lipid content, especially triglycerides, was estimated after the addition of ORI to the free fatty acid cell model for 24 h. Furthermore, studies revealed that ORI can enhance autophagy and decrease the liver cells steatosis (Cheng et al., 2021 ). Similarly, ORI, combined with ginsenoside and the fungus Ganoderma lucidum , is reported to enhance immunological processes and ultimately the apoptosis in hepatocellular carcinoma (HCC) cells (He et al., 2021 ).…”
Section: Current Medical Applications – Official Treatment or Traditi...mentioning
confidence: 99%
“…The drug was found to be effective in inhibiting the progression of HCC by targeting multiple pathways. Moreover, the drug was found to be safe during the acute toxicity tests [ 96 ].…”
Section: Liver Targeting Strategy Of Rg3mentioning
confidence: 99%
“…The ginsenoside Rg3, oridonin, and Ganoderma lucidum polysaccharide (GLP) were introduced into a self-microemulsifying drug delivery system (RGO-SMEDDS) as an anti-angiogenic agent, immune regulator, and apoptosis inducer, respectively. The system evinced a combined strategy against HCC via triggering angiogenesis inhibition, anti-proliferation, and decreasing immunosuppressive cytokines and M2-polarized macrophages, for the suppression of the p-EGFR/AKT/GSK3 axis ( He et al, 2021 ).…”
Section: Pharmaceutical Delivery Systems Against Tumor Angiogenesismentioning
confidence: 99%